Made-to-order power. - Shenai, K.
The author describes how, when circuit and device designers jointly tailor power electronics systems to a specific application, performance and reliability can benefit at little or no cost
Keywords: Application; Circuit design; Device design; Made-to-order power; Performance; Power electronics systems; Reliability